From Playboy to Prison: When Pornography Use Becomes a Crime. Issue 1 (2nd January 2021) - Garman, Julie D.; Sample, Lisa L.; Steele, Sarah A.
ABSTRACT: This study explores pornography use across the lifespan for a sample of registrants convicted of child pornography related offenses. We conducted qualitative life history interviews with nine offenders to examine how offender, victim, and situational factors interact to produce pornography-related criminal events. Using a hybrid analytic approach, themes related to persistence in pornography use and the social acceptability of pornography are identified. These themes relate to transitions from legal pornography use to illegal child pornography possession.